2019
DOI: 10.3341/kjo.2018.0034
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy in Type 2 Diabetic Retinopathy Requiring Panretinal Photocoagulation

Abstract: PurposeTo investigate the risk factors of diabetic nephropathy in patients with diabetic retinopathy requiring panretinal photocoagulation (PRP) and the visual prognosis.MethodsA retrospective review of electronic medical records was conducted at Seoul St. Mary's Hospital, comprising 103 patients with type 2 diabetes mellitus and diabetic retinopathy who underwent PRP from 1996 to 2005. Patients with type 1 diabetes mellitus, non-diabetic renal disease, non-diabetic retinal disease, visually significant ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
15
0
2
Order By: Relevance
“…Previous work has found that multiple distinct miRNAs can modulate the progression of DN via targeting a wide range of signaling pathways relating to autophagy, oxidative and mechanical stress, and advanced glycation end-product generation (Chung, 2015;Nascimento & Domingueti, 2019). A range of interrelated factors including genetics, ischemia, inflammation, and hypoxia have all been found to contribute to DN progression (Ha, Choi, Kim, Na, & Park, 2019;Xu, Natarajan, & Chen, 2019 (Barutta et al, 2013;Huang et al, 2014). In this study, we found that miR-218 also regulated inflammatory signaling in a Inflammation is a central regulatory process governing DN pathogenesis, with inflammatory factors including IL-1, IL-6, and TNF-α all being linked to the development of this disease (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has found that multiple distinct miRNAs can modulate the progression of DN via targeting a wide range of signaling pathways relating to autophagy, oxidative and mechanical stress, and advanced glycation end-product generation (Chung, 2015;Nascimento & Domingueti, 2019). A range of interrelated factors including genetics, ischemia, inflammation, and hypoxia have all been found to contribute to DN progression (Ha, Choi, Kim, Na, & Park, 2019;Xu, Natarajan, & Chen, 2019 (Barutta et al, 2013;Huang et al, 2014). In this study, we found that miR-218 also regulated inflammatory signaling in a Inflammation is a central regulatory process governing DN pathogenesis, with inflammatory factors including IL-1, IL-6, and TNF-α all being linked to the development of this disease (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in line with other studies’ findings [ 1 , 7 , 10 ]. Such conduct is essential because prevention, early diagnosis, and effective treatment of many comorbidities, such as hypertension, hyperlipidemia, or heart disease, exert a significant impact on DR development and progression [ 9 , 12 , 16 , 27 ]. We found that 54% of DR patients suffer from hyperlipidemia, and 68% suffer from hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It emphasizes the importance of preventive screening of such comorbidities and regular monitoring of DR progression. Furthermore, DR is not the only complication of diabetes, as it also leads to various disorders such as chronic kidney disease, lower extremity ischemia, coronary heart disease, neuropathy, stroke, myocardial infarction, depression, and many others [ 1 , 3 , 7 , 8 , 9 , 10 , 11 , 28 , 29 ]. We found that DR patients significantly more often undergo several medical examinations to diagnose these life-limiting and life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations